Computerspiel- und Internetsucht ein kognitiv-behaviorales Behandlungsmanual - Wölfling, Klaus 1971-; Beutel, Manfred 1955-; Bengesser, Isabel; Müller, Kai W. 1979- (Verlag W. Kohlhammer, 2022)
Following its inclusion in ICD-11, the addictive use of computer games has now found its way into health care as a recognized new disorder. Other forms of addictive Internet behaviour can now also be coded as diagnoses, at least indirectly. The Outpatient Department for Gambling Addiction in Mainz has a long tradition in the research and treatment of behavioural addictions and has pioneered the development of appropriate interventions. This manual provides scientifically well-based and practical information on diagnosis and treatment and describes a validated form of behavioural therapy treatment in detail. The work is rounded off with case studies and downloadable materials for treatment. Mit der Aufnahme in die ICD-11 hat die suchtartige Nutzung von Computerspielen als neues Störungsbild Eingang in die Gesundheitsversorgung gefunden. Auch andere Formen internetsüchtigen Verhaltens lassen sich nun, zumindest indirekt, als Diagnosen verschlüsseln. Die Ambulanz für Spielsucht Mainz weist eine langjährige Tradition in der Forschung und Behandlung von Verhaltenssüchten auf und ist führend in der Entwicklung von entsprechenden Interventionen. Das Manual informiert wissenschaftlich fundiert und praxisbezogen über Diagnostik und Therapie und beschreibt im Detail eine evaluierte verhaltenstherapeutische Behandlung. Fallbeispiele und Therapiematerialien zum Download runden das Werk ab